Evaluation of strength development in cemented dredged sediment admixing recycled glass powder. (1st August 2022) - Zhang, Xinlei; Li, Desheng; Lang, Lei
Highlights: Recycled glass powder (GP) can be used as Portland cement (PC) admixture in dredged sediment (DS) stabilization. The effects of PC content, GP content, GP fineness and curing age on the strength development of PC-GP stabilized DS (CGDS) were investigated. The optimum GP content inside CGDS tended to increase with the curing age evolution. Incorporating suitable GP contributed to the formation of dense cemented soil matrix inside CGDS. Abstract: Using glass powder (GP) as Portland cement (PC) helper in dredged sediment (DS) stabilization can achieve the double benefit of reducing PC dosage and recycling waste GP. This study evaluated the feasibility of using GP together with PC in improving the strength properties of DS. The effects of PC content, GP content, GP fineness and curing age on the strength development of PC-GP stabilized DS (CGDS) were investigated via a series of unconfined compressive strength (UCS) tests. Furthermore, scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests were conducted to analyze the strength evolution micro-mechanisms inside CGDS. The results showed that the UCS of CGDS increased monotonously with increasing PC content, and incorporating GP led to the strength gain of CGDS regardless of PC content. The optimum GP content tended to increase with increasing curing age and water content. The highest 28-day UCS of CGDS with water content of 50, 60 and 75% were respectively achieved at GP content of 15, 15 and 20%. Improving GP fineness can obviously improve the strength development of CGDS. The maximum strength growth rate (UCSgr ) of CGDS with water content of 50, 60 and 75% were respectively achieved at PC content of 8, 8 and 10%, and increasing GP content and fineness resulted in UCSgr improvement. The 28-day UCS of CGDS can be predicted via the known 7-day UCS using proposed linear relation. The microstructural test results confirmed that incorporating suitable GP contributed to the formation of dense cemented soil matrix inside CGDS. The 10% PC admixing 15–20% GP with 2000-mesh number fineness is recommended to replace 15% PC for stabilizing DS containing 50–75% water content.